Évaluation comparée de l’apport de l’assistance GPS aux enquêtes de mobilité - Guillaume Drevon; Francis Jambon; Sonia Chardonnel; Sidonie Christophe; Isabelle André-Poyaud; Paule-Annick Davoine; Céline Lutoff (Netcom)
Travel surveys can collect information about practices and behaviours of individual mobility. These surveys and the resulting analyses are necessary for the development and evaluation of public transport policies. Usually, these surveys use traditional methods for data collection with standard survey methods. Today, new survey protocols and data collection methods emerge thanks to the potential of new technologies. Geo-localization technologies, such as GPS, can be an interesting support for new types of so-called "assisted" surveys. However, these technologies may provide new types of challenges in the context of surveys with representative samples of the population. Furthermore, the use of location technologies requires modifying significantly the survey protocols. To identify the potential benefit of geo-localization technologies for travel surveys, we conducted a comparative study between a classic travel survey (Household Travel Survey) and a GPS assisted travel survey. This comparative evaluation also allowed us to identify the main technological and methodological limitations of GPS assisted travel surveys.